Pleural empyema after COVID-19: A delayed presentation (Indian Journal of Case Reports, 2024)
Globally, the number of coronavirus disease-2019 (COVID-19) cases and deaths shows a declining trend since a peak in January 2022. For now, the pandemic phase looks to be ended, until a severe new variant may trigger another wave. At present, in India, small pockets of COVID-19 cases and post-COVID complications are still being reported. Therefore, physicians should remain vigilant about the atypical presentations and potential delayed or long-term complications of SARS-CoV-2 infection, even in individuals who had a mild COVID-19 infection. Here, we present the case of a 52-year-old male patient with a history of hypertension, who is a non-smoker and developed culture-negative pleural empyema 7 months after a mild COVID-19 infection. The patient was successfully treated with antibiotics and early video-assisted thoracoscopic surgery.